Continuous Hyperfractionated Accelerated Radiotherapy (CHART) for Non-small Cell Lung Cancer (NSCLC): 7 Years' Experience From Nine UK Centres. Issue 3 (March 2018) - Sanganalmath, P.; Lester, J.E.; Bradshaw, A.G.; Das, T.; Esler, C.; Roy, A.E.F.; Toy, E.; Lester, J.F.; Button, M.; Wilson, P.; Comins, C.; Atherton, P.; et al.
Abstract: Aim: Continuous hyperfractionated accelerated radiotherapy (CHART) remains an option to treat non-small cell lung cancer (NSCLC; NICE, 2011). We have previously published treatment outcomes from 1998–2003 across five UK centres. Here we update the UK CHART experience, reporting outcomes and toxicities for patients treated between 2003 and 2009. Materials and methods: UK CHART centres were invited to participate in a retrospective data analysis of NSCLC patients treated with CHART from 2003 to 2009. Nine (of 14) centres were able to submit their data into a standard database. The Kaplan–Meier method estimated survival and the Log-rank test analysed the significance. Results: In total, 849 patients had CHART treatment, with a median age of 71 years (range 31–91), 534 (63%) were men, 55% had undergone positron emission tomography-computed tomography (PET-CT) and 26% had prior chemotherapy; 839 (99%) patients received all the prescribed treatment. The median overall survival was 22 months with 2 and 3 year survival of 47% and 32%, respectively. Statistically significant differences in survival were noted for stage IA versus IB (33.2 months versus 25 months; P  = 0.032) and IIIA versus IIIB (20 months versus 16 months; P  = 0.018). Response at 3 months and outcomes were significantly linked; complete response showing survival of 34 months against 19 months, 15 months and 8 months for partial response, stable and progressive disease, respectively ( P  < 0.001). Age, gender, performance status, prior chemotherapy and PET-CT did not affect the survival outcomes. Treatment was well tolerated with <5% reporting ≥grade 3 toxicity. Conclusion: In routine practice, CHART results for NSCLC remain encouraging and we have been able to show an improvement in survival compared with the original trial cohort. We have confirmed that CHART remains deliverable with low toxicity rates and we are taking a dose-escalated CHART regimen forward in a randomised phase II study of sequential chemoradiotherapy against other accelerated dose-escalated schedules. Highlights: Confirms the schedule is deliverable in daily practice with low levels of toxicity. Improving outcomes when compared with the original CHART trial publications. Hyperfractionated accelerated radiotherapy fractionations are worthy of further study in the locally advanced NSCLC population.